Taxonomy in watercolor: the Specklinia endotrachys group, part 2 - Pupulin, Franco (2013)
in the last decade orchid systematics has focused especially on assessing evolutionary relationships among species and species groups, in an attempt to produce a solid phylogenetic framework for the family. While in general this effort has been amply successful, the results of phylogenetic analyses applied to the nomenclature of some groups are still much debated. This situation is particularly evident in the case of the Pleurothallid orchids, where several schemes of classification, based in part on different data sets — but sometimes on discordant interpretations of the same data, both molecular and non-molecular —, are in current use. As a partial consequence of the ardent debate on alternative phylogenetic hypotheses, with the inevitable shifting of the discussion on the side of generic circumscriptions and naming, less attention has been paid to the correct interpretation of the species and the diversity within groups. Species delimitation, however, remains an essential activity not only in systematics, but also in taxonomic and evolutionary studies, and the identification of the boundaries between closely related species is an essential target of current systematics (PESSOA et al. 2012). The plants discussed and illustrated in this article well exemplify this point, while they show how different approaches and the use of a broad spectrum of different tools (including molecular markers), or integrative taxonomy, help depicting complex genetic and morphological variation patterns.